Answer:
1. Substitute y = -3x +4 for y in the first equation
2. Combine like terms and isolate x
3. Substitute in x into the 2nd equation to get y
Step-by-step explanation:
1. Substitute y = -3x +4 for y in the first equation
2x- (-3x+4) = 6
2. Combine like terms
5x -4 = 6
5x -4 +4 = 6+4
5x=10 Divide by 5 to isolate x
5x/5 =10/5
x=2
3. Substitute in x into the 2nd equation to get y
y = -3x +4
y = -3(2) +4
y = -6+4
y=-2
(2,-2)
The reciprocal is just the fraction flipped over. 7/6 flipped is 6/7.
Answer:
Step-by-step explanation:
To solve using completing square, we need to write the equation as x2+3x=17.
The next step is to add a number such that the square can be completed. The number must be equal to (b/2a)^2, so here it will be (3/2)^2 = 9/4
The equation then becomes x2+3x+(9/4)=17+(9/4).
Solving it further will get you the final answer
Answer:
90
Step-by-step explanation: